2020
DOI: 10.1136/bjophthalmol-2020-316296
|View full text |Cite
|
Sign up to set email alerts
|

SD-OCT peripapillary nerve fibre layer and ganglion cell complex parameters in glaucoma: principal component analysis

Abstract: Background/aimsTo identify objective glaucoma-related structural features based on peripapillary (p) and macular (m) spectral domain optical coherence tomography (SD-OCT) parameters and assess their discriminative ability between healthy and glaucoma patients.MethodsTwo hundred and sixty eyes (91 controls and 169 glaucoma) were included in this prospective study. After a complete examination, all participants underwent the posterior pole and the peripapillary retinal nerve fibre layer (pRNFL) protocols of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Multiple quantitative retinal imaging techniques comprising scanning laser polarimetry, Heidelberg retinal tomography, as well as optical coherence tomography (OCT) [8][9][10][11][12][13] , have been utilized to measure RNFL thickness. Among them, spectral-domain optical coherence tomography (SD-OCT), which is the latest generation of OCT, provides a high-resolution and enhance-depth visualization of the retina and the ONH [14][15][16] . With the utilization of SD-OCT in daily routine diagnosis, several studies have demonstrated that the attenuation of average pRNFL thickness is common in NAION and glaucoma [5,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] , where NAION may mimic with POAG [34] .…”
Section: Oct Differentiates Naion and Poagmentioning
confidence: 99%
“…Multiple quantitative retinal imaging techniques comprising scanning laser polarimetry, Heidelberg retinal tomography, as well as optical coherence tomography (OCT) [8][9][10][11][12][13] , have been utilized to measure RNFL thickness. Among them, spectral-domain optical coherence tomography (SD-OCT), which is the latest generation of OCT, provides a high-resolution and enhance-depth visualization of the retina and the ONH [14][15][16] . With the utilization of SD-OCT in daily routine diagnosis, several studies have demonstrated that the attenuation of average pRNFL thickness is common in NAION and glaucoma [5,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] , where NAION may mimic with POAG [34] .…”
Section: Oct Differentiates Naion and Poagmentioning
confidence: 99%
“… 24 And third, the selection of parameters to create a composite score can be challenging: choosing different indicators from the same source and with analogous behavior can lead to multicollinearity, where many variables contain similar information that is, therefore, redundant. In this situation principal component analyses 7 or unit-weighted composite scores would be more suitable, 25 and fewer properly selected variables would be probably more precise as well. 26…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Lately, several combinations of these parameters have proven to improve the diagnostic ability of isolated OCT parameters, especially in early glaucoma. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…This anatomical separation makes it possible to study the retinal ganglion cells by direct imaging using optical coherence tomography (OCT) and consider it as a window into different physiological and pathological processes in the brain (1)(2)(3)(4)(5)(6). The measurement of the RNFL has been thoroughly investigated in different diseases such as glaucoma (7), idiopathic intracranial hypertension (IIH) (8) and optic neuritis (9); on the other hand, the GCL has also been measured and investigated as the retinal ganglion cell complex (GCC), which includes both the ganglion cell layer and the inner plexiform layer (IPL) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%